Individual Characteristics and Employee Performance in a BUMD: Evidence from Kupang City - Rolland Epafras Fanggidae; Ni Putu Nursiani (Goodwood Publishing, 2026)
Purpose: This study examines the influence of individual characteristics on employee performance in a Regional-Owned Enterprise (BUMD), namely, the Regional Public Market Company of Kupang City, with work discipline and organizational commitment as moderating variables. Methodology: An explanatory quantitative approach with a cross-sectional design was employed. Data were collected from 158 employees using a structured questionnaire measured on a five-point Likert scale. The data were analyzed using Moderated Regression Analysis (MRA) with SPSS 25.0 to test both direct and interaction effects. Results: Individual characteristics significantly influence employee performance. The inclusion of work discipline as a moderating variable increased the explanatory power to 37.4%, and organizational commitment further strengthened the model to 66.0%, indicating a substantial moderating effect. Conclusions: Individual characteristics positively affect employee performance, and this relationship becomes stronger when supported by higher levels of work discipline and organizational commitment. Limitations: This study focused on a single local government enterprise, limiting its generalizability. Contributions: Nevertheless, it contributes to the literature on public sector human resource management and offers practical insights for BUMD management in improving recruitment, discipline systems, and commitment-based performance strategies.